2021
DOI: 10.2478/foecol-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of gelling agents on in vitro organogenesis and some physicochemical properties of date palm buds, Showathy cv.

Abstract: Some obstacles are associated with in vitro propagation of date palm, such as explant tissue browning, slow callus growth and development, low organogenesis and multiplication efficiency, and frequent tissue vitrification. This investigation studied the effect of five types of gelling agents (Danish Agar, Cero Agar Type 8952, Chile Agar, Gerlite Food Grade, and Agar-Agar.) on in vitro regeneration and bud multiplication of Phoenix dactylifera L. cv. Showathy. The results showed that the highest percentages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…3), with significant differences compared to other treatments. Browning is one of the problems facing the practical applications of date palm propagation in vitro, and eliminating or minimizing this phenomenon is essential to establishing a successful culture (Al-Mayahi et al, 2020;Al-Mayahi and Ali, 2021). Phenolic compounds production is correlated with the browning intensity of date palm tissues cultures, and many authors proved these findings in their studies (Al-Mayahi et al, 2018;Shehata et al, 2014), however, Mustafa et al (2013) demonstrated that high concentrations of auxins led to accumulating of phenolic compounds and inhibited the growth of cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), with significant differences compared to other treatments. Browning is one of the problems facing the practical applications of date palm propagation in vitro, and eliminating or minimizing this phenomenon is essential to establishing a successful culture (Al-Mayahi et al, 2020;Al-Mayahi and Ali, 2021). Phenolic compounds production is correlated with the browning intensity of date palm tissues cultures, and many authors proved these findings in their studies (Al-Mayahi et al, 2018;Shehata et al, 2014), however, Mustafa et al (2013) demonstrated that high concentrations of auxins led to accumulating of phenolic compounds and inhibited the growth of cultures.…”
Section: Discussionmentioning
confidence: 99%
“…With all these facts, in vitro propagation is the most promising method for the rapid propagation of date palms to overcome the decline in the number of desirable cultivars (Al-Mayahi, 2019;Abdalla et al, 2022). Plant tissue culture effectivity as a means of plant propagation is greatly affected by selecting the proper culture medium (Al-Mayahi et al, 2010;Al-Mayahi and Ali, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For the improvement of rooting ability of cuttings from adult individuals, the effect of more factors, such as the auxin type and the concentration, the substrate composition (ratio of mixture of perlite:peat), the rooting system (fog, aeroponic system) on cutting rooting needs to be investigated. Furthermore, as an alternative to propagation by cuttings, in vitro techniques (Al-Mayahi et al, 2020;Konopkova et al, 2020;Al-Mayahi and Ali, 2021) could be used for an optimal multiplication of T. baccata adult individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, many studies have shown that the type of gelling agent used can influence tissues growth in vitro (Quiala et al, 2014;Ramassamy, 2014, 2015;Al-Mayahi, 2015;Raina, 2017;Hegele et al, 2021, therefore the study on selecting commercial grades of gelling agents is very important. There are limited studies about gelling agent effect routinely used in micropropagation on palm plant growth and development (Al-Mayahi, 2021;.…”
Section: Introductionmentioning
confidence: 99%